Intra-industry trade, specialisation and business cycles in ASEAN - Cortinhas, Carlos (2005)
Recently, a new resolve for both increased economic integration and monetary and exchange rate cooperation has started to emerge in ASEAN, especially since the 1997-1998 Asian financial crisis. According to the optimum currency area theory, the degree of trade integration is one most important criterion for joining a currency union. The large increase in intra-ASEAN trade in recent years naturally raises the question of whether the ASEAN countries are becoming better prepared to form a currency union. This paper sets to test whether the recorded increase in intra-ASEAN trade is leading the ASEAN members to closer economic integration and thus to better satisfy the criteria for a common currency. Two separate models are estimated for that purpose. First, a variation of the model of Frankel and Rose (1997) was estimated for the ASEAN members. As the results were not very significant, a new methodology that uses the whole sample period data instead of dividing the data into sub-periods was conducted. The results with our own model were very significant and robust, and showed a clear positive correlation between intra-industry trade and business cycle synchronization in ASEAN. This result has important implications for the prospects of the creation of a common currency in the region.